Metal Conservation Method in The Infinity Statue by Dunadi - Ratnaningtyas, Yohana Ari; Purwanto, Tambak Sihno; R, Luna Chantiaya; T, Geminisya Aldeana (Journal of Urban Society's Arts, 2024)
The Infinity Sculpture by Dunadi is a media representation of the idea of the eternal function of bicycles over time. The infinity statue is primarily made of ferrous metal, so it has the potential for damage in the form of patina and rust, especially when exposed to direct sunlight, rainwater, oxygen, and other substances that accelerate corrosion growth. The current condition of the infinity statue by Dunadi could be better because most of the paint has peeled off, and rust has grown on the entire surface of the metal that is not covered with paint. This article discusses the application of modern metal conservation methods to Dunadi’s Infinity Sculpture. This study’s contemporary metal conservation method compares several synthetic chemicals to clean rust on metal and then apply it to Dunadi’s Infinity Statue. The synthetic chemicals used are some of the rust-cleaning agents available. Synthetic chemicals are available because they are easy to obtain and relatively safe. We tested Several brands of rust cleaners available on the market on metal objects similar to the material for making infinity statues. As a result, the most effective rust- cleaning chemicals contain hydrochloric acid. Patung Infinity karya Dunadi merupakan representasi media dari gagasan tentang fungsi abadi sepeda dari waktu ke waktu. Patung infinity utamanya terbuat dari logam besi, sehingga berpotensi mengalami kerusakan berupa patina dan karat, terutama jika terkena sinar matahari langsung, air hujan, oksigen, dan zat lain yang mempercepat pertumbuhan korosi. Kondisi patung infinity karya Dunadi saat ini bisa lebih baik karena sebagian besar catnya sudah terkelupas, dan karat sudah tumbuh di seluruh permukaan logam yang tidak dilapisi cat. Artikel ini membahas penerapan metode konservasi logam modern pada Patung Infinity karya Dunadi. Metode konservasi logam kontemporer dalam penelitian ini membandingkan beberapa bahan kimia sintetis untuk membersihkan karat pada logam lalu mengaplikasikannya pada Patung Infinity karya Dunadi. Bahan kimia sintetis yang digunakan merupakan beberapa bahan pembersih karat yang tersedia. Bahan kimia sintetis tersedia karena mudah diperoleh dan relatif aman. Kami menguji beberapa merek pembersih karat yang tersedia di pasaran pada benda logam yang mirip dengan bahan untuk membuat patung infinity. Hasilnya, bahan kimia pembersih karat yang paling efektif mengandung asam klorida.